Perancangan Stool Set Dengan Deformasi Bentuk Tripod Kamera Sebagai Alternatif Pilihan Mebel Baru: perancangan - drajad wibowo (Penerbit Itenas, 2023)
Furniture is not only a complementary element of home furnishings for both interior and exterior, but can give a special impression to the user. This research aims to design a furniture design that can provide the best choice according to the user's taste, both in terms of characteristics and raw materials. The design of the stool set design with the stages of deformation of the shape of the tripod uses the Stages of Thinking method approach which has six stages, namely: (1) Design Brief, (2) Research Backgroud, (3) Design Resolve, (4) Select Rationale, (5) Implement Delevery, (6) Learn Feedback. is to apply elements of tripod legs & camera lens to the stool set product. Qualitative research with data collection through field observations, interviews with craftsmen and shop owners, as well as the media. Product design is a process that begins with the discovery of problems and ideas. Then, data is collected and evaluated, a design concept is decided, alternative designs are sketched, and the design is selected. This research-based design is a source of learning and alternative choices for furniture that has unique ideas and good materials